(untitled) (PerCursos, 2022)
The traditional street market, that happens on Sundays in the city of Marília, located in the interior of the state of São Paulo, was moved to the margin of the central region in 2015 by the interests of the Universal Church of the Kingdom of God with the mediation of the public power. However, this dispute is not an isolated happening, it developed in the contemporary urban context, which is mostly guided by the neoliberal interests of the real estate market. With the intention of demonstrating the relationship between the change of the fair and the urban development influenced by real estate capital, this article presents an analysis of the dispute using two analytical categories, spontaneous spaces and sterile spaces, which were developed by qualitative research on spaces of the city that are directly and indirectly related to the street open market. These spaces, selected through interviews with marketer and their customers were the Tauste supermarket, the Marília Shopping and the Urban bus terminal. The categories contributed to locating the street market in the city’s web of social relations and to understand the meaning of its displacement for the urban development project in medium-sized cities. Therefore, the approximation of the street market with the spontaneous spaces category and the Universal Church with sterile spaces category indicates the degree of conformity of the city of Marília with the tendency of a neoliberal city project, whose model has been present for decades in the great urban centers of the country.